Editors' Introduction: Aligning Implicit Learning and Statistical Learning: Two Approaches, One Phenomenon. (23rd July 2019) - Rebuschat, Patrick; Monaghan, Padraic
Abstract: This editors' introduction provides the background to the special issue. We first outline the rationale for bringing together, in a single volume, leading researchers from two distinct, yet related research strands, implicit learning and statistical learning. The aim of the special issue is to facilitate the development of a shared understanding of research questions and methodologies, to provide a platform for discussing similarities and differences between the two strands, and to encourage the formulation of joint research agendas. We then introduce the new contributions solicited for this special issue and provide our perspective on the agenda setting that results from combining these two approaches. Abstract : In their editors' introduction, Rebuschat and Monaghan provide the background to the special issue. They outline the rationale for bringing together, in a single volume, leading researchers from two distinct, yet related research strands, implicit learning and statistical learning. The editors then introduce the new contributions solicited for this special issue and provide their perspective on the agenda setting that results from combining these two approaches.